AN ANALYTICAL STUDY OF MARITAL ADJUSTMENT OF WORKING WOMEN WITH SPECIAL REFERENCE TO THEIR FINANCIAL INDEPENDENCE (A STUDY IN PUNJAB, PAKISTAN) - AAMNA SALEEM BAJWA; YASIR NAWAZ MANJ; RAB NAWAZ (Innovare Journal of Social Sciences, 2025)
In Pakistan, marital adjustment is a topic for research having great importance for sociologists, psychologists, and some other social researchers. Marriage is culturally, socially legitimate relation among two individuals begin with a public type of announcement and having some ideas of stability it is understood with additional a fewer explicit marriage agreement, which spells out the give-and-take human rights and obligations stuck between the spouses and future children. The family is a communal unit that appears to be based on marital adjustment. The different national and international organization and university scholars have been working on this social issue. The main objectives of the research are as “To assess the degree of impact of financial independence of working women on marital adjustment. As the main hypothesis of the research is having same future aspiration leads towards a balanced marital adjustment, it’s analyzed through different statistical tools such as percentage; chi-square, gamma test univariate, and bi-variate were applied to assess the association among the different hypothesis. As for the methodology is concern, convenience is proposed for this research. A sample of 400 married working women was selected from four districts Jhang, Bukhar, Khushab, and Sargodha. Some reliability checks were also adopted to ensure the consistency of the data by all means at all levels. It was found that 54.0% of respondents strongly agreed that financial matters solved by mutual understanding of husbands and wives. Data shows that 50.5% respondents strongly agreed that they are usually good to resolve their problems at own their best satisfaction level. It is suggested that on the basis of this study as, marriage seminar and workshops which could help minimize disunity in families should often be organized by the government and marriage counselors and couples of various sort should be encouraged to attend.